2022
DOI: 10.1016/j.ekir.2021.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Change Disease Is Associated With Endothelial Glycocalyx Degradation and Endothelial Activation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…SARS-CoV-2 and mRNA vaccines have been associated with endothelial injury. Interestingly, recent studies have shown alterations in the glomerular endothelium in patients with MCD, suggesting that MCD associated with SARS-CoV-2 vaccination may in part be ascribed to glomerular and systemic endothelial disfunction [ 30 , 31 , 32 ]. It is worth noting that the response to the standard therapy for MCD has been suggested to be worse when it occurs around the same time as COVID-19 vaccination [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 and mRNA vaccines have been associated with endothelial injury. Interestingly, recent studies have shown alterations in the glomerular endothelium in patients with MCD, suggesting that MCD associated with SARS-CoV-2 vaccination may in part be ascribed to glomerular and systemic endothelial disfunction [ 30 , 31 , 32 ]. It is worth noting that the response to the standard therapy for MCD has been suggested to be worse when it occurs around the same time as COVID-19 vaccination [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on such changes ( 23 ) has demonstrated that in addition to changes in podocytes, the disappearance of endothelial cell fenestrations and the disappearance of the cytoplasmic honeycomb sieve structure of endothelial cells is also visible, and it is believed that patients with changes in endothelial cells might have a poor prognosis. Bauer et al ( 24 ) suggested that alterations involving the systemic and glomerular endothelium are nearly universal in patients with MCD, and that Glomerular endothelial cell can be directly activated by circulating factors present in the MCD sera during relapse. The above literature suggests that in terms of the pathological changes in kidneys in NS, in addition to foot process effacement, changes in endothelial cells and the basement membrane may also be involved in the pathogenesis and process of NS.…”
Section: Discussionmentioning
confidence: 99%
“…damage [17]. Similarly, acute kidney damage with transient proteinuria could be caused by locally activated heparinases in kidney that degrade the glycocalyx leading to a diminished glomerular filtration barrier and vascular leakage [18 & ].…”
Section: Kidney Diseasementioning
confidence: 99%
“…When the glomerular endothelial glycocalyx is damaged, the endothelium and podocytes are exposed to the circulating factors within the blood, leading to albuminuria [16]. Indeed, patients with podocyte disorders have an increase in syndecan-1, heparin sulfate in the blood, as well as enhanced heparinase activity, indicating glycocalyx degradation [17]. Glycocalyx degradation in these conditions is accompanied by von Willebrand factor and thrombomodulin release into the blood that may also contribute to podocyte damage [17].…”
Section: Kidney Diseasementioning
confidence: 99%